Chapter Il laboratorio intellettuale di Bruno Trentin (2001-2006) - Cruciani, Sante (Studi e saggi, 2021)
A selection of Trentin'sdiaries from 2001-2006, some unpublished pages on his political activity in the European Parliament and the elaboration of The Freedom Comes First: these works allow us to enter Bruno Trentin's intellectual laboratory and to follow, from the inside, the editing of the essays and the realization of the volume. Public and private intertwine in a melee with a heavy depression, which demands to "cope with death by accelerating the production of writings that can clarify or conclude my testimony." The notes on the Italian and international situation after September 11th, 2001, the American intervention in Iraq in 2003 and the European Constitution project are significant. The section is completed by some coeval political interventions, including the last article of July 2006 on meritocracy and the affirmation of individual rights.